2022
DOI: 10.1021/acssensors.2c00980
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized CO2 Gas Sensor Using 20% ScAlN-Based Pyroelectric Detector

Abstract: NDIR CO 2 gas sensors using a 10-cm-long gas channel and CMOS-compatible 12% doped ScAlN pyroelectric detector have previously demonstrated detection limits down to 25 ppm and fast response time of ∼2 s. Here, we increase the doping concentration of Sc to 20% in our ScAlN-based pyroelectric detector and miniaturize the gas channel by ∼65× volume with length reduction from 10 to 4 cm and diameter reduction from 5 to 1 mm. The CMOS-compatible 20% ScAlN-based pyroelectric detectors are fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 53 publications
3
18
1
Order By: Relevance
“…The pyroelectric coefficients obtained from our in‐house AlN and 12%‐doped ScAlN are comparable with those reported in literature. [ 15,39,42,48,56,57 ] It is also worthwhile to note that the pyroelectric coefficients calculated for AlN and 12% ScAlN are in general independent of background temperatures, agreeing with what Kurz et al. [ 48 ] have reported.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The pyroelectric coefficients obtained from our in‐house AlN and 12%‐doped ScAlN are comparable with those reported in literature. [ 15,39,42,48,56,57 ] It is also worthwhile to note that the pyroelectric coefficients calculated for AlN and 12% ScAlN are in general independent of background temperatures, agreeing with what Kurz et al. [ 48 ] have reported.…”
Section: Resultssupporting
confidence: 86%
“…The pyroelectric coefficients obtained from our in-house AlN and 12%-doped ScAlN are comparable with those reported in literature. [15,39,42,48,56,57] It is also worthwhile to note that the pyroelectric coefficients calculated for AlN and 12% ScAlN are in general independent of background temperatures, agreeing with what Kurz et al [48] have reported. This is because the AlN and 12%-doped ScAlN films deposited in this work are columnar and do not contain abnormally oriented grains (AOGs) that usually resulted in bigger grains in the film.…”
Section: Aln-and 12% Scaln-based Pyroelectric Detectors Gas Sensing R...supporting
confidence: 88%
See 1 more Smart Citation
“…Optics-based methods have several advantages and are widely used in trace gas monitoring. Non-dispersive infrared (NDIR) has been increasingly applied to atmospheric CO 2 and H 2 O monitoring [ 5 , 6 , 7 ]. However, the application of NDIR is limited because it uses a broadband light source and therefore has poor selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…They are compact and can function at room temperature without the need for liquid nitrogen (N2) cooling, unlike photon detectors which usually require cooling. 4 Their thermal sensing capability is widely used for a number of applications including gas sensing, [5][6][7] temperature sensing, [8][9][10] ultraviolet/ infrared (UV/ IR) light detection, [11][12][13][14][15] thermal imaging [16][17] etc. When considering using pyroelectric detectors in contactless button system, they could potentially replace the traditional way contactless button works.…”
Section: Introductionmentioning
confidence: 99%